2014
DOI: 10.1039/c3ra44338h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and high-performance of a new sarcosinate anionic surfactant with a long unsaturated tail

Abstract: A new C 22 tailed sarcosinate anionic surfactant, 2-(N-erucacyl-N-methyl amido) acetate (EMAA), has been synthesized by use of the erucic acid and a hydrotrope-sarcosine. In contrast to the common method, which blends the hydrotrope with a surfactant, the sarcosine has been introduced into the anionic surfactant through chemical modification. Interestingly, the resultant C 22 tailed anionic surfactant shows excellent water solubility despite the ultra-long alkyl chain. Besides, the EMAA also exhibits high surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The aqueous phase viscosity has been increased by adding high concentrations of inorganic salts for amine oxide zwitterionic surfacants and for polymers with carboxybetaines monomers. 44,45,46,47 The decrease in a o with salinity may be expected to produce longer and more entangled wormlike micelles, 16,22,48,49 as was also evident in the decrease in the crossover frequency in Figure 3.…”
Section: Resultsmentioning
confidence: 85%
“…The aqueous phase viscosity has been increased by adding high concentrations of inorganic salts for amine oxide zwitterionic surfacants and for polymers with carboxybetaines monomers. 44,45,46,47 The decrease in a o with salinity may be expected to produce longer and more entangled wormlike micelles, 16,22,48,49 as was also evident in the decrease in the crossover frequency in Figure 3.…”
Section: Resultsmentioning
confidence: 85%
“…In addition, engineering responsiveness to two, three of more individual stimuli and convoluted combinations of them allow a high degree of control on functionality, which is of particular interest for instance to fine-tune drug release profiles or to achieve delivery of a payload in specific compartments of the body. While still a field in its early stage, the majority of multi-stimuli-responsive materials reported to date have been polymeric in nature [17][18][19][20][21][22], only a few systems based on small molecular assemblies have been described very recently [21,23,24], among which just a very few studies dealing with multi-stimuli-responsive WLMs, which are discussed below.…”
Section: Multi-stimuli-responsive Wlmsmentioning
confidence: 98%
“…This long-chain anionic surfactant shows pH-controllable micelle-vesicle-WLM transition. Besides pH, the rheological properties of EMAA are also affected by temperature and salt [24].…”
Section: Multi-stimuli-responsive Wlmsmentioning
confidence: 99%
“…Yang et al [32] synthesized a C22-tailed sarcosinate anionic surfactant, 2-(N-erucacyl-N-methyl amido) acetate (EMAA) and observed that its solutions display a pH-controllable transition from micelles to vesicles. In rheological experiments, when increasing the pH from 6.43 to 7.36, η 0 showed a substantial increase from 3.8 to 222.5 Pa s.…”
Section: Ph-responsive Wlms Obtained From the Design Of Surfactant Armentioning
confidence: 99%